Facilitating access to iCBT: a randomized controlled trial assessing a translated version of an empirically validated program using a minimally monitored delivery model. Issue 2 (16th March 2020) - Robichaud, Miguel; Talbot, France; Titov, Nickolai; Dear, Blake F.; Hadjistavropoulos, Heather D.; Hadjistavropoulos, Thomas; Jbilou, Jalila
Abstract: Background: Despite its established efficacy, access to internet-delivered CBT (iCBT) remains limited in a number of countries. Translating existing programs and using a minimally monitored model of delivery may facilitate its dissemination across countries. Aims: This randomized control trial aims to evaluate the efficacy of an iCBT transdiagnostic program translated from English to French and offered in Canada using a minimally monitored delivery model for the treatment of anxiety and depression. Method: Sixty-three French speakers recruited in Canada were randomized to iCBT or a waiting-list. A French translation of an established program, the Wellbeing Course, was offered over 8 weeks using a minimally monitored delivery model. Primary outcome measures were the Generalized Anxiety Disorder-7 (GAD-7) and the Patient Health Questionnaire-9 (PHQ-9), which were obtained pre-treatment, post-treatment and at 3-month follow-up. Results: Mixed-effects models revealed that participants in the treatment group had significantly lower PHQ-9 and GAD-7 scores post-treatment than controls with small between-groups effect sizes (d = 0.34 and 0.37, respectively). Within-group effect sizes on primary outcome measures were larger in the treatment than control group. Clinical recovery rates on the PHQ-9 and GAD-7 were significantly higher among the treatment group (40 and 56%, respectively) than the controls (13 and 16%, respectively). Conclusions: The provision of a translated iCBT program using a minimally monitored delivery model may improve patients' access to treatment of anxiety and depression across countries. This may be an optimal first step in improving access to iCBT before sufficient resources can be secured to implement a wider range of iCBT services.